Behavioral diversity is maintained by a conditional strategy in a freshwater zooplankton. (10th April 2019) - Meyer, G Adam; Nelson, William A
Abstract : Populations often live in heterogeneous environments, which can allow for different types of migration behavior. Using a natural population of freshwater zooplankton, we show experimentally that distinct migration behaviors experience equal fitness, despite occupying vastly different environments. However, the physiological conditions necessary for success in one behavior lead to reduced growth in the opposite behavior. Thus, environmental heterogeneity allows for multiple behaviors, but a physiological trade-off makes switching behaviors costly. Abstract: Many populations have intraspecific diversity in phenotype and ecological strategy, but the mechanisms maintaining such diversity are not fully understood. Multiple behaviors can be maintained either as a conditional strategy, where fitness depends on an individual's phenotype, or as a mixed strategy, where alternative behaviors have similar fitness independent of phenotype. Using high-resolution depth and time sampling, we characterize 2 distinct diel vertical migration behaviors in a population of freshwater zooplankton ( Daphnia pulicaria ). Individuals in this population differ in their color phenotype and migratory behavior with red morphs upregulating hemoglobin and undergoing a deep migration and pale morphs not producing hemoglobin and undergoing a shallow migration. We experimentally manipulated the behavior of each phenotype in the field and measured population growth in their natural migration behavior as well as population growth in their alternative behaviors. Experimental populations of pale and red morphs under their natural migrations had roughly equal fitness, despite vast differences in environmental conditions. When forced to switch behaviors, pale morphs suffered reduced fitness, whereas red morphs had similar fitness compared with their natural migration. Our results suggest that although behavioral diversity may be promoted by the opportunity for alternative behaviors of equal fitness, the distinct physiological conditions required for survival in alternative behaviors limit the capacity for individual behavioral switching and likely maintain behavioral diversity as a conditional strategy.